Effects of Local Specialization of Investment Subsides in Italy - Francesco Losurdo; Annamaria Stramaglia (European Regional Science Association (ERSA), 2003)
In Italy we currently have a lot of national and regional instruments for financial aids to enterprises. Most of them are not specialized, as syntethetized in the following points: 1. they are refferred to the whole Italian territory; 2. they have generic objects (increase of GNP, reduction of growth differences among regions, employment); 3. they are applied to all the sectors of production; 4. they have common methods of application (automatic, discretional,negotiated). This means that we establish general purposes without further specialization even if we fall into particular purposes.In addition to this types of subsides, there are anymore that are specialized both at territorial and at sectorial level. Among these, the most important are distributed by the Territorial Pacts that are one of the instruments of concerted planning. In this paper we firstly define the specialization of some forms of subsidies; then we analize the performance of two samples of enterprises, that are located in the Apulia Region (NUTS III), the first of which has been benefiting from the state support provided by law n.488/92 (Financial support of the productive activities in depressed zones), and the second one that has been benefiting from the support provided by Territorial Pacts. The enterprises performance have been assessed through quantitative index measured by three main relations: 1. Sales / Assets, that is an indicator measuring the firms efficiency. So it indicates if the total value of sales they?ve carried out, can account for the effectuated investments. 2. Profit / Sales, that estimate the enterprise ability to obtain profits, aging in the market, and let us having indications about prospects of success. 3. Profit / Assets, that assess, in a better way, the capacity in terms of global income of the enterprise. Comparing the average of the three indicators considered, related to supported enterprises, with the same indexes of Mediobanca sample about not-supported enterprises, we obtain interesting results. They have proved that: A. the enterprises having supports are, generally, less efficient than those having no support; B. the firms subsided by Territorial Pacts are more efficient than the other ones subsided by law n.488/92. From the investigation it emerges that the subsides territorially oriented are more efficient than the general support, referred to the same area. So, if we privilege efficiency results, putting the effectiveness ones in a secondary position, we probably should prefer an automatic but specialized aid system, at least from the territorial, dimensional and productive point of view according to preference scales. But, if we want to obtain effectiveness standards too, it is necessary to specialize the interventions and determine specific goals and result indicators.
Keywords: 330